Gods prophet,Gods servant: a study in Jeremiah and Isaiah 40-55 - GOLDINGHAY ,John 1984 (Great Britian The Paternoster Press, 1984)
In God's Prophet, God's Servant, John Goldingay examines the portrait of a prophet's ministry found in Jeremiah and the portrait of a servant's ministry in Isaiah 40-55, showing us that in both cases, God calls us to a deeper and more demanding view of ministry
Jeremiah ,Isaiah
index
Keywords: Jeremiah,Isaiah